Ações para melhoria da satisfação dos clientes em uma cooperativa de crédito - Sartori, Simone (2009)
This dissertation has for objective to present actions of improvement of satisfaction customers in a Cooperative of Credit. The research was accomplished with associated, employees and the director the Cooperative, located in city of Santa Maria/RS. The research possesses qualitative nature, once the bases on the interpretation of the processes related with the rendered services. Quantitative, because made use of the scale SERVQUAL and analysis the Modelo GAP, under the optics the seven dimensions of quality: Physical aspects, Reliability, Responsividade, Empathy, Access, Safety and Speed. Later, starting from the obtained data, the dimensions were measured, identifying the flaws in the service, and defined the improvement opportunities, above all, to contribute in creation of services that are totally gone back to the customers' satisfaction. In general, the results point that a good level the satisfaction exists in relation to the services rendered by cooperative. According to the associates evaluation, the largest levels of quality demands dimensions related to: Access, Speed and Tangible Aspects; for employees, the dimensions are: Access and Responsividade. Starting from the found results, intend improvement actions for the customer satisfaction in order to have a cycle of continuous improvement.